WANPRESTASI, KEGAGALAN TRANSAKSI DAN PERLINDUNGAN KONSUMEN DALAM TRANSAKSI ELEKTRONIK - Gunawan Widjaja; Viony Kresna Sumantri; Shella Felicia; Raissa Arlyn Manikam (Cross-border, 2019)
Default in Electronic Transactions is generally the same as default in general. Forms of Default Through the Internet or Electronic Transactions are: Not doing what is promised to be done; Carry out what was promised, but not in accordance with what was promised; Carry out what was promised but was late and Carry out something that according to the agreement should not be done.